Penyelesaian Sengketa India-China melalui Mahkamah Internasional - Andy Christopher Fallen; Efie Baadila; Josina Agusthina Yvonne Wattimena (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Aksai Chin is a region located in the border between India and China territories. This particular region has been in dispute for two countries since the Sino-Indian War in 1962. India holds on a demarcation line; passed down by England colony; a line called McMahon Line. Meanwhile China holds on different line called Line of Actual Control (LAC). The two countries do not share same perspective on demarcation line until these days. Plenty of agreements and treaties were made but did not produce expected result for both countries. The conflict occurred once again with the latest incident happened in Aksai Chin border when the border patrols of both countries were attacking each other.Purposes of the Research: This event triggered some questions regarding how to put an end to this international dispute. The aims of this research are to provide a resolution to end the long dispute between India and China, to find out the middle ground or the better solution. Methods of the Research: Type of research used is juridical normative, that is concept of law that is textual (law in books) or concept of law as a norm as guidance to how society behave in proper manner, by using case approach, statue approach and conceptual approach.Results of the Research: In this research it was concluded that in international law there has been a regulation on how to set the boundaries of a country. The basis for determining borders, namely unwritten provisions and provisions. In recent developments, state boundaries are more determined by sources and processes of international law, such as self-determination, the principle of uti possidetis juris, effective occupation, state succession and national boundary agreements. The most potential mechanism for this case is through the International Court of Justice, first it is because the International Court of Justice (ICJ) is much more practical because it has permanent judges who are recognized. Second, with the International Court of Justice (ICJ) if a party in the case does not fulfill the obligations imposed by the ICJ decision, the other party can directly call the attention of the World Security Council if necessary to request a recommendation or determine the actions taken to make the decision possible.